CORRELATION AND PATH COEFFICIENT ANALYSIS IN LINSEED (LINUM USITATISSIMUM L.) - B. RAJANNA; S.A. BIRADAR; K. AJITHKUMAR (The Bioscan, 2014)
The present study was conducted on variability, correlation and path coefficient analysis for yield and yield contributing characters in linseed. The highest genotypic coefficient of variation was observed for 1000 seed weight (29.48) and high heritability coupled with high genetic advance was observed for 1000 seed weight (0.99 and 60.45) and seed yield (0.85 and 35.40). The results of phenotypic and genotypic correlation analysis revealed that number of capsules plant-1 (0.797 and 0.704), was significantly and positively correlated with seed yield and plant height (0.2 and 0.192) and technical plant height (0.204 and 0.198) was positively correlated with seed yield in present material. Path analysis indicated that number of capsules plant-1 (0.7615) exhibited high direct positive effect on seed yield signifying the importance of this trait while selecting for improvement of seed yield of linseed.